Design and simulated performance of a solar-thermal system employing seasonal storage for providing the majority of space heating and domestic hot water heating needs to a single-family house in a cold climate. (October 2019) - Beausoleil-Morrison, Ian; Kemery, Briana; Wills, Adam D.; Meister, Curtis
Highlights: Solar with seasonal storage can provide majority of space/water heating in cold-climate houses. Annual solar fractions for space/water heating in order of 90 A building-scale system with evacuated collectors and a buried water store has been designed. Seasonal-store insulation, weather fluctuations, and occupant behaviour are most impactful. Abstract: The majority of the space and domestic hot water heating needs of houses in cold climates can be supplied by solar energy, but only if long-term (seasonal) storage is employed to enable solar energy collected during the summer and autumn to be used during winter. Most seasonal storage applications to date have been for community-scale systems, although there have been a few experimental and simulation studies of building-scale applications, which offer reduced losses from transmission networks due to the proximity between building-mounted solar collectors and the seasonal store. A simulation-based study has been performed to design a building-scale solar thermal system with seasonal storage for a research house with a heated floor area of approximately 150 m 2 . Parametric simulations revealed that a solar fraction exceeding 90% could be achieved for many combinations of solar collector area and seasonal store volume. A solar collector gross area of 41.6 m 2 and a seasonal store volume of 36 m 3 were chosen for this installation, which is expected to achieve a solar fraction in the range of 87–98%.